Perilaku Merokok Sebagai Identitas Sosial di Kalangan Pelajar Kacamatan Tanjungpinang Timur - Wisnu Rudika; Shelly Rahmadani Putri; Casiavera Casiavera (Faculty of Social and Political Science Universitas Maritim Raja Ali Haji, Indonesia, 2023)
This study aims to find out how the process of forming adolescent smoking behavior as a social identity in Tanjungpinang. This study seeks to examine the tendency of adolescent smoking behavior which is used as an identity in adolescent social interactions. Both serve as symbols of virility and approval. This research is a case study using a qualitative approach using data collection techniques, namely interviews, observation and library research. The data obtained was then divided into two categories, secondary data and primary data, which were then processed and presented in a descriptive form to describe the research as a whole. The findings show that smoking, which was originally only reserved for adult men, is now commonplace among teenagers. In society, smoking is a sign of one's maturity, so that teenagers also have smoking behavior. At first teenagers were influenced to smoke because apart from seeing smoking habits in society, especially men smoking, inviting friends to smoke was also one of the factors that influenced teenagers to smoke.